An exploration of how schools and teachers interpret and implement the Language in Education Policy for their classroom practice: a case study - Sibanda, Sikhumbuzo (Rhodes University, Faculty of Education, Department of Education)
This case study explored how schools and teachers interpret and implement the Language in Education Policy for their classroom practices. Scholars like Alexander and Block (2012) note that the South African Language in Education Policy (LiEP) is one of the advanced policies globally. Other scholars like Perry (2015) and Ngcobo (2015) state that the policy in South Africa has failed when it comes to implementation. It is against this background that the research explored how schools and teachers interpret and implement the Language in Education Policy for their classroom practice in three primary schools in Kuruman, Northern Cape. The research methodology was qualitative and it used a case study approach. The study is informed and framed by the Language Policy framework and the CDA (Critical Discourse Analysis). The research sites were three Grade 4 classes and the participants were three teachers, three principals and three SGB Chairpersons from three different schools (one school in deep rural, another in semi-urban and the third in urban) in Kuruman. This case study, located in the interpretive paradigm, employed individual semi-structured interviews, non-participant classroom observations, document analyses and field notes for data collection. The study revealed that teachers are not versed in LiEP and their classroom practice is therefore not based on policy but on their own perceptions. Classroom practices were incongruent with what the Language in Education Policy requires. Even other documents which support the Language in Education Policy like the school language policies, were not used as guiding documents for classroom practice. Lastly, this study revealed that, despite a plethora of literature on how practice engages and disengages with Language in Education Policy (LiEP), the deconstruction of colonial and apartheid education is still a challenge especially in language use, perceptions of mother tongue instruction and the hegemony of English. One of the recommendations of this study is that teachers must be taught to use Languages of Learning and teaching required in their areas and they should also be given continuous professional development courses on policies so as to improve their practice. Language Policy Units should be set up within the provincial and district Departments of Education that would support the implementation of LiEP.
Keywords: Language policy -- South Africa; Education and state -- South Africa; Critical discourse analysis; Native language and education -- South Africa Kuruman; Educational change -- South Africa; South Africa Colonial influence; South African Language in Education Policy